2001
DOI: 10.1073/pnas.201404898
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effect of bacillus Calmette–Guérin (BCG) vaccination on Mycobacterium tuberculosis infection in highly related macaque species: Implications for primate models in tuberculosis vaccine research

Abstract: Despite the widespread use of bacillus Calmette-Gué rin vaccination, Mycobacterium tuberculosis infection remains globally the leading cause of death from a single infectious disease. The complicated and often protracted dynamics of infection and disease make clinical trials to test new tuberculosis vaccines extremely complex. Preclinical selection of only the most promising candidates is therefore essential. Because macaque monkeys develop a disease very similar to humans, they have potential to provide impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
129
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 36 publications
(24 reference statements)
13
129
4
Order By: Relevance
“…In this study, in situ protein levels as well as the survival of the BCG/ rAd35-vaccinated animals were similar compared with the unvaccinated control NHPs, which may suggest that the prime vaccine must enable phagolysosomal escape of mycobacterial proteins in the cytosol to effectively trigger CD8 + T cells and enhance immune protection. It has previously been shown that the BCG vaccine cannot protect rhesus macaques from developing progressive TB disease, whereas cynomolgus monkeys were almost completely protected by BCG (58). Interestingly, the immune response in animals with poor prognosis was associated with higher Mtb antigen load and an increased proportion of CD68 + macrophages in the Mtb infected tissue, but also with a decreased CTL response.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, in situ protein levels as well as the survival of the BCG/ rAd35-vaccinated animals were similar compared with the unvaccinated control NHPs, which may suggest that the prime vaccine must enable phagolysosomal escape of mycobacterial proteins in the cytosol to effectively trigger CD8 + T cells and enhance immune protection. It has previously been shown that the BCG vaccine cannot protect rhesus macaques from developing progressive TB disease, whereas cynomolgus monkeys were almost completely protected by BCG (58). Interestingly, the immune response in animals with poor prognosis was associated with higher Mtb antigen load and an increased proportion of CD68 + macrophages in the Mtb infected tissue, but also with a decreased CTL response.…”
Section: Discussionmentioning
confidence: 96%
“…Albert Calmette and Camille Guérin followed Pasteur's strategy of mimicking the natural response to infection using an attenuated pathogen to produce the BCG vaccine (87). An extensive literature attests to the fact that prior exposure to BCG vaccine accelerates development of the adaptive immune response to M. tuberculosis in animal models, conferring advantages in terms of reduced mycobacterial load and increased time to death (88)(89)(90)(91). The same pattern can be seen in humans in the context of severe forms of childhood TB (92).…”
Section: Vaccinesmentioning
confidence: 99%
“…Here, we tested this vaccine in non-human primate models, which are important in evaluating immunogenicity, safety, and efficacy of new vaccine candidates due to their close phylogenetic relationship with humans. Cynomolgus macaques are susceptible to M. tuberculosis, and the outcome of infection clinically and pathologically resembles that of human infection (20)(21)(22)(23). We tested H56 in both highand low-dose challenge models, as a boost to BCG.…”
Section: Introductionmentioning
confidence: 99%